Power electronic converters for solar photovoltaic systems - Kumar, L. Ashok; Albert Alexander, S.; Rajendran, Madhuvanthani (Academic Press, 2021)
Power Electronic Converters for Solar Photovoltaic Systems provides design and implementation procedures for power electronic converters and advanced controllers to improve standalone and grid environment solar photovoltaics performance. Sections cover performance and improvement of solar photovoltaics under various conditions with the aid of intelligent controllers, allowing readers to better understand the nuances of power electronic converters for renewable energy systems. With algorithm development and real-time implementation procedures, this reference is useful for those interested in power electronics for performance improvement in distributed energy resources, design of advanced controllers, and measurement of critical parameters surrounding renewable energy systems. By providing a complete solution for performance improvement in solar PV with novel control techniques, this book will appeal to researchers and engineers working in power electronic converters, renewable energy, and power quality.